Altered cellular metabolism of HepG2 cells caused by microcystin-LR. (June 2017) - Ma, Junguo; Feng, Yiyi; Jiang, Siyu; Li, Xiaoyu
Abstract: This study aimed to evaluate the possible effects of microcystin-LR (MC-LR) exposure on the metabolism and drug resistance of human hepatocellular carcinoma (HepG2) cells. For this purpose, we first conducted an experiment to make sure that MC-LR could penetrate the HepG2 cell membrane effectively. The transcriptional levels of phase I (such as CYP2E1, CYP3A4, and CYP26B1) and phase II (such as EPHX1, SULTs, and GSTM) enzymes and export pump genes (such as MRP1 and MDR1) were altered by MC-LR-exposure for 24 h, indicating that MC-LR treatment may destabilize the metabolism of HepG2 cells. Further research showed that the CYP inducers omeprazole, ethanol, and rifampicin inhibited cell viability, in particular, ethanol, a CYP2E1 inducer, induced ROS generation, lipid peroxidation, and apoptosis in HepG2 cells treated with MC-LR. The CYP2E1 inhibitor chlormethiazole inhibited ROS generation, mitochondrial membrane potential loss, caspase-3 activity, and cytotoxicity caused by MC-LR. Meanwhile, the results also showed that co-incubation with the ROS scavengerl -ascorbic acid and MC-LR decreased ROS levels and effectively prevented apoptosis. These findings provide an interesting mechanistic explanation of cellular metabolism associated with MC-LR, i.e., MC-LR-exposure exerted toxicity on HepG2 cells and induced apoptosis of HepG2 cells via promoting CYP2E1 expression and inducing excessive ROS in HepG2 cells. Graphical abstract: Highlights: MC-LR could penetrate HepG2 cell membrane effectively. MC-LR-exposure disturb the metabolic destabilization of HepG2 cells. CYP2E1 plays an important role in cellular metabolism of HepG2 cells caused by MC-LR. Abstract : The linkage between CYP2E1-dependent oxidative stress and mitochondrial injury contributes to the toxic action of MC-LR on HepG2 cells.